Applied multimodal diagnostics in a case of presenile dementia. Issue 1 (December 2016) - Schönecker, Sonja; Brendel, Matthias; Huber, Marion; Vollmar, Christian; Huppertz, Hans-Juergen; Teipel, Stefan; Okamura, Nobuyuki; Levin, Johannes; Rominger, Axel; Danek, Adrian
Abstract Background Alzheimer's disease (AD) is the most common cause of dementia in the elderly. The possibility of disease-modifying strategies has evoked a need for early and accurate diagnosis. To improve the accuracy of the clinical diagnosis of AD, biomarkers like cerebrospinal fluid (CSF) and neuroimaging techniques like magnetic resonance imaging (MRI) and positron emission tomography (PET) have been incorporated into the diagnostic guidelines of AD. Case presentation In this case report we outline in reference to one of our patients with presenile dementia the current approaches to the diagnosis of AD. The patient was a 59-year old woman presenting with progressive memory decline. CSF-Aβ42 was normal while P-tau was slightly increased. FDG-PET indicated a pattern typical for AD, amyloid-PET showed an extensive global amyloid load, and tau-PET depicted a pronounced hippocampal tracer accumulation. The MRI scan was rated as normal at routine diagnostics, however quantitative volumetric analysis revealed significant atrophy especially of the parietal lobe. The combination of biomarkers and neuroimaging techniques was therefore suggestive of an underlying AD pathology. Conclusions To enable early and accurate diagnosis of AD and thereby also patient recruitment for anti-tau or anti-β-amyloid therapeutic trials, a combination of biomarkers and neuroimaging techniques seems useful.